1955
DOI: 10.6028/jres.055.025
|View full text |Cite
|
Sign up to set email alerts
|

Determination of natural rubber in GR-S - natural rubber vulcanizates by infrared spectroscopy

Abstract: ;\ rap id m ethod for t he estimation of natural r ubber in vulcani zates of GR-S a nd nat ura l rubber by m eans of infra red spectrosco py is reported . Sampl es were carefully prepared to co ntal!1 known amou nts of .natural and GR-S rubber; the samples \I'ere v ulcan ized, extracted wL t h acetone, and dn ed III a vac u um oven. Specim ens from eac h sam ple were pyr olyzed in a combu st ion furn ace at 550 0 C. and the liquid pyrolyzates were a nalyzed by mfra red absorptLOn spectroscop y . An e mpLL"lcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1958
1958
1984
1984

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Other infrared spectrophotometric studies have been made but no quantitative measurements were reported (3)(4)(5)(6).…”
Section: Resultsmentioning
confidence: 99%
“…Other infrared spectrophotometric studies have been made but no quantitative measurements were reported (3)(4)(5)(6).…”
Section: Resultsmentioning
confidence: 99%
“…SBR/NR. Further study (94) of pyrolysis followed by infrared measurement (148) showed that the absorbance ratio of bands at 889 and 909 cm.-1 was a function of the vulcanization recipe when pyrolysis was done at 550°C. However, when the temperature was increased to 950°C ., six different curing systems gave variations of only ±1.3% (94).…”
Section: Determination Of Polymers In Polymer Mixtures and Constituen...mentioning
confidence: 99%
“…Other infrared spectrophotometric studies have been made but no quantitative measurements were reported (3)(4)(5)(6).…”
mentioning
confidence: 99%